GAMELAN SEBAGAI SARANA MEMULIAKAN ALLAH - WIGUNA, VINCENTIUS AGSUKO (Felicitas, 2022)
In Indonesia, diversity needs to be respected as well as the elements on it. One of themis art. Art displays a unique form of existence in the culture of society. This papertargets the art of Javanese musical instruments, namely Gamelan. In context, the useof Gamelan musical instruments in churches on the Java is not a strange thing.Gamelan is used to accompany the songs in the Eucharistic Celebration. In this paper,the author wants to explore and reflect on Gamelan as a means of glorifying God. Thediscussion of this paper will lead to the context of the Church in Asia, an explanationof music in the Church, about Gamelan music, and theological reflection on gamelanas a means of glorifying God.